Wendell Fertig and his guerrilla forces in the Philippines fighting the Japanese occupation, 1942-1945 - Holmes, Kent 1933- (McFarland & Company, Inc., Publishers, 2015)
"Creating a guerrilla movement to fight the Japanese occupation of the Philippines (1942-1945) presented Colonel Wendell Fertig with some formidable challenges. Unlike the other islands in the archipelago, Mindanao had a large Moslem population. By using Moro and American leadership he was able to bring the Moro people into the movement. Fertig lacked communication with MacArthur"--